Integrated Thematic Teaching Materials Based on Local Wisdom to Develop the Elementary School Students’ Characters (Universitas Negeri Semarang, 2022)
The study aims at developing, analyzing validity, testing efficiency, assessing practicality, and describing student character development using the integrated teaching materials based on Sugiyono's model of R&D research approach. The subjects were the fourth-grade students of State Elementary School of Ngemplak, Simongan 02 Semarang City. The data technically collected using the techniques of interviews, documentation, questionnaires, and tests and are analyzed using product feasibility, t test and N gain test. The results showed that; (1) the integrated thematic teaching materials covers Semarang's local wisdom of cultural tourism, traditional cuisine, attractive color illustrations and character-building learning activities; (2) These materials are considered feasible. The level of eligibility criteria for the first validator was 89.50 % and the second validator is 91.75 % (very feasible); (3) the integrated thematic teaching materials were used effectively referring to results of the t test which indicate that t count > t table (6.67 > 2.57) and assisted by gain test which obtained 0.678 as moderate criteria; (4) the rate of student teaching material practicality at 97,88 % (very positive) and the ratio of teacher responses at 96,87 % (very positive), and (5) integrated thematic teaching materials based on local wisdom can develop the questionnaire character. This concludes that integrated thematic teaching materials are highly appropriate for learning, enhance student learning effectively, are practical and can enhance student characters.